Crystallization and preliminary X-ray diffraction analysis of central structure domains from mumps virus F protein - Liu, Yueyong (International Union of Crystallography, 2005)
Fusion of members of the Paramyxoviridae family involves two glycoproteins: the attachment protein and the fusion protein. Changes in the fusion-protein conformation were caused by binding of the attachment protein to the cellular receptor. In the membrane-fusion process, two highly conserved heptad-repeat (HR) regions, HR1 and HR2, are believed to form a stable six-helix coiled-coil bundle. However, no crystal structure has yet been determined for this state in the mumps virus (MuV, a member of the Paramyxoviridae family). In this study, a single-chain protein consisting of two HR regions connected by a flexible amino-acid linker (named 2-Helix) was expressed, purified and crystallized by the hanging-drop vapour-diffusion method. A complete X-ray data set was obtained in-house to 2.2 Å resolution from a single crystal. The crystal belongs to space group C2, with unit-cell parameters a = 161.2, b = 60.8, c = 40.1 Å, β = 98.4°. The crystal structure will help in understanding the molecular mechanism of Paramyxoviridae family membrane fusion.